The Pyrazolone Originally Reported to Be a Formyl Peptide Receptor (FPR) 2/ALX-Selective Agonist Is Instead an FPR1 and FPR2/ALX Dual Agonist - Yoshitaka Sogawa; Akiko Shimizugawa; Takao Ohyama; Hiroaki Maeda; Kazuki Hirahara (Elsevier, 2009)
A pyrazolone compound acting as a formyl peptide receptor (FPR) 2/ALX-selective agonist has been reported, but its pharmacological activities on human FPRs (hFPRs) and mouse FPRs (mFprs) have not been well demonstrated. In this study, we found that this compound, designated as compound A, induced concentration-dependent calcium flux not only in Chinese hamster ovary (CHO) cells expressing hFPR2/ALX but also in cells expressing hFPR1, mFpr1, or mFpr2. It also induced the receptor internalization of hFPR1 and hFPR2/ALX and, accordingly, induced calcium influx and chemotactic responses in both human and mouse neutrophils. Our study revealed that compound A is in fact an FPR1 and FPR2/ALX dual agonist. Keywords:: formyl peptide receptor, neutrophil, chemotaxis